P-041 Enhanced procedural guidance during deployment of flow-diverters using 3D land marking and overlay technique. (4th July 2012) - Durai, P Chinna; Chintalapani, G; Shaltoni, H; Morsi, H; Mawad, M
Abstract : Purpose: Endoluminal parent vessel reconstruction using flow-diverting device has emerged as a viable alternative to stent-assisted coiling/surgical clipping in wide necked intracranial aneurysms. 1 Accurate device positioning in parent vessel and deployment technique directly influences the degree of metal surface area coverage across the aneurysm ostium and thereby the extent of flow-diversion. Unlike self-expanding stents with terminal radio-opaque markers, fluoroscopic visibility of these first generation flow-diverter devices is limited. We propose a 3D land marking and overlay technique to provide enhanced guidance during deployment of these flow-diverters under fluoroscopy. Methods: We obtained a 3D-DSA image using the following protocol: 5s-DSA, 18 cc contrast injected at 2.5 cc/s, 2 s x-ray delay. The aneurysm ostium and origin of relevant branches such as the anterior choroidal artery are electronically marked in the reconstructed images using syngo iGuide Toolbox application (Siemens AG, Healthcare Sector, Forchheim, Germany). The resulting image is then overlaid on the real-time 2D fluoroscopy or roadmap image inside the procedure room ( syngo iPilot, Siemens AG, Healthcare Sector, Forchheim, Germany). Results: After ensuring 2D-3D registration accuracy, the overlay of 3D-DSA image (along with electronic anatomical markers) on 2D fluoroscopic images was used in a total of 20 Pipeline flow-diverter cases during deployment (Abstract P-041 figure 1 ). The superimposition of 3D-DSA image with vascular markers on real-time native fluoroscopy, adds relevant information during flow-diverter deployment without the need for additional contrast injection. Specifically, the knowledge about relationship of the flow-diverter to aneurysm ostium in a 3D-space during deployment was helpful in increasing the metal coverage across aneurysm ostium by compacting the device. The relationship of flow-diverter device to relevant vascular branching point markers during deployment helped in minimizing unnecessary coverage of these vessels with the device. Conclusions: Fluoroscopic visibility of flow-diverter is limited in real-time native fluoroscopic images. The proposed 3D overlay and landmarking technique provides a platform to fuse the information from 3D-DSA images with real-time fluoroscopic images for enhanced visualization of the flow diverter stents during deployment. Additionally, such 3D overlay with electronic markers can be controlled from inside the procedure room and is adjusted dynamically with various C-arm angulations, without the need for additional contrast injections. Competing interests: P Chinna Durai: Full-time employee. G Chintalapani: Full-time Employee. H Shaltoni: None. H Morsi: None. M Mawad: Siemens Medical Solutions USA Inc. Reference: 1. Fiorella D, et al. Curative cerebrovascular reconstruction with the Pipeline embolization device: the emergence of definitive endovascular therapy for intracranial aneurysms. J NeuroInterv Surg 2009;1 :56–65.